Review of the Pressure Swing Adsorption Process for the Production of Biofuels and Medical Oxygen: Separation and Purification Technology - Jesse Y. Rumbo Morales; Gerardo Ortiz-Torres; Rodolfo Omar Domínguez García; Carlos Alberto Torres Cantero; Manuela Calixto Rodriguez; Estela Sarmiento-Bustos; Edén Oceguera-Contreras; Alberto Arturo Flores Hernández; Julio César Rodríguez Cerda; Yehoshua Aguilar Molina; Mario Martínez García (Adsorption Science & Technology)
The production of biofuels has had a great impact on climate change and the reduction of the use of fossil fuels. There are different technologies used for the separation and production of biofuels, which allow having compounds such as ethanol, methane, oxygen, and hydrogen, one of these promising technologies is the Pressure Swing Adsorption process (PSA). The objectives of this article focus on the production and purification of compounds that achieve purities of 99.5% bioethanol, 94.85% biohydrogen, 95.00% medical oxygen, and 99.99% biomethane through the PSA process; also, a significant review is contemplated to identify the different natural and synthetic adsorbents that have greater adsorption capacity, the different configurations in which a PSA operates are studied and identified, and the different mathematical models that describe the dynamic behavior of all the variables are established that interact in this PSA process, parametric studies are carried out in order to identify the variables that have the greatest effect on the purity obtained. The results obtained in this review allow facilitating the calculation of parameters, the optimization of the process, the automatic control to manipulate certain variables and to achieve the rejection of disturbances to have a recovery and production of biofuels with a high degree of purity.